'Hallervorden-Spatz syndrome - infantile neuroaxonal dystrophy' complex: case report - A. U. Bresolin; L. Pascuzzi; R. Melaragno Filho; Maria H. Fontana; R. Pécora; J. C. Souza Dias (Arquivos de Neuro-Psiquiatria)
Case report of a 7 1/2-years old girl considered as being normal until the age of 2 years. From then on she progressed with gait disturbance, mental deterioration, dystonic movements, convulsions and dysarthria. She died of bronchopneumonia one year later. CT scan showed hyperdensity at the putamina, with no signs of cerebral atrophy. Pathological examination disclosed an intense red coloration of the putamina and axonal «spheroids» at electron microscopy.